Characterization of ExeM, an Extracellular Nuclease of Shewanella oneidensis MR-1 - Binnenkade, Lucas; Kreienbaum, Maximilian; Thormann, Kai M. (Frontiers in Microbiology, 2018)
Bacterial extracellular nucleases have multiple functions in processes as diverse as nutrient acquisition, natural transformation, biofilm formation, or defense against neutrophil extracellular traps (NETs). Here we explored the properties of ExeM in Shewanella oneidensis MR-1, an extracellular nuclease, which is widely conserved among species of Shewanella, Vibrio, Aeromonas, and others. In S. oneidensis, ExeM is crucial for normal biofilm formation. In vitro activity measurements on heterologously produced ExeM revealed that this enzyme is a sugar-unspecific endonuclease, which requires Ca2+ and Mg2+/Mn2+ as co-factors for full activity. ExeM was almost exclusively localized to the cytoplasmic membrane fraction, even when a putative C-terminal membrane anchor was deleted. In contrast, ExeM was not detected in medium supernatants. Based on the results we hypothesize that ExeM predominantly interacts with DNA in close proximity to the cell, e.g., to promote biofilm formation and defense against NETs, or to control uptake of DNA.